2016
DOI: 10.2514/1.j054114
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Analysis of Projectiles in Ground Effect at Near-Sonic Mach Numbers

Abstract: The behavior of projectiles at Mach 0.9, 1.1, and 1.2 when in close proximity to a surface were investigated using a synergy of live-range test firings, wind-tunnel experiments, and computational fluid dynamics simulations; the latter provided the majority of the insight into the problem. Building on work that previously indicated significant ground influence for a projectile at Mach 2.4 due to shock reflections, a similar projectile was investigated for ground clearances of height-to-diameter ratios from 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Doig et al, analyzed projectile behavior by using CFD simulation, wind tunnel and synergy live range fire testing at Mach 0.9, Mach 1.1 and Mach 1.2 [11]. It was observed that normal force, drag force and pitching moment change predictably at Mach 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…Doig et al, analyzed projectile behavior by using CFD simulation, wind tunnel and synergy live range fire testing at Mach 0.9, Mach 1.1 and Mach 1.2 [11]. It was observed that normal force, drag force and pitching moment change predictably at Mach 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…Although many near space hypersonic vehicles, such as X-37 (Gülhan et al, 2014), X-51 (Schimisseur, 2015) and Falcon HTVs (Walker et al, 2008), have been succeeded in their missions, the exploration of aerothermodynamic problems is the principle obstacle because the velocities and altitudes at which these vehicles would operate are different, and sometimes more severe (Huang and Huang, 2015;Hu et al, 2016aHu et al, , 2016bLi et al, 2016), than those went through in the past. As future hypersonic vehicle quests to fly higher and faster, the environment surrounding the vehicle could be more dramatically changed (Hu et al, 2016a(Hu et al, , 2016bCai 2016;Yuan et al, 2017) and more difficult to simulate in ground-based test facilities (Doig et al, 2016), which makes the numerical simulations become increasingly important issues (Park et al, 2016;Boyd et al, 2010). Whether the existing numerical methods can apply to higher velocity is an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%